BUILDING CHARACTER IN ISLAMIC EDUCATION PERSPECTIVE - Ahmad Faqihuddin (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2021)
Building Character in the Perspective of Islamic Education. Character education is education to shape one's personality, through education that Indonesians are familiar with, namely character, behavior, honesty, responsibility, respect for others, hard work, and so on, which is an important education to develop one's character. This character education involves aspects of knowledge (cognitive), feelings (feeling), and action (action). These three aspects are the unity that makes the action real in human behavior. The existence of problems in society such as crime, drugs, violence between students, widespread corruption, domestic violence is evidence of a crisis of national identity. The answer is the existence of character education to answer these problems. Islamic religious education is the spirit of character education through the development of akhlaqul karimah, human morals are formed with noble values ​​and religious teachings. Those values ​​must be expressed in one's amaliah. Therefore, character education through religious education is very important for the Indonesian people who are famous for being religious. Pendidikan karakter adalah pendidikan untuk membentuk kepribadian seseoranag, melalui pendidikan yang orang Indonesia tidak asing lagi yaitu budi pekerti, tingkah laku, kejujuran, tanggung jawab, menghormati orang lain, kerja keras, dan sebagainya merupakan pendidikan yang penting untuk mengembangkan karakter seseorang. Pendidikan karakter ini melibatkan aspek pengetahuan (cognitive), perasaan (feeling), dan tindakan (action). Ketiga aspek merupakan kesatuan yang menjadikan perbuatan itu nyata dalam tingkah laku manusia. Adanya persoalan di masyarakat misalnya kriminalitas, narkoba, kekerasan antar pelajar, semaraknya korupsi, kekerasan dalam rumah tangga merupakan bukti adanya krisis jati diri bangsa. Sebagai jawabannya adalah adanya pendidikan karakter untuk menjawab permasalahan tersebut. Pendidikan agama Islam merupakan ruh dari pendidikan karakter melalui pembinaan akhlaqul karimah, moral manusia dibentuk dengan nilai-nilai luhur dan ajaran agama. Nilai-nilai itu harus dinyatakan dalam amaliah seseorang. Oleh karena itu, pendidikan karakter melalui pendidikan agama sangat penting untuk bangsa Indonesia yang terkenal religius.